2021
DOI: 10.1002/aic.17466
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli to produce and secrete colicins for rapid and selective biofilm cell killing

Abstract: Bacterial biofilms are associated with chronic infectious diseases and are highly resistant to conventional antibiotics. Antimicrobial bacteriocins are alternatives to conventional antibiotics and are characterized by unique cell-killing mechanisms, including pore formation on cell membranes, nuclease activity, and cell wall synthesis inhibition. Here, we used cell-free protein synthesis to rapidly evaluate the antibiofilm activities of colicins E1, E2, and E3. We found that E2 (with DNase activity) most effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The potential for anti-bacterial toxins to be engineered and utilised for therapeutical purposes has also been explored. A recent study showed that colicins can be used to disrupt biofilm integrity [223]. Moreover, when injected into the bloodstream of mice, pyocin S5 was observed to retain its functionality and to improve mouse survival to Pseudomonas infections [224].…”
Section: Discussionmentioning
confidence: 99%
“…The potential for anti-bacterial toxins to be engineered and utilised for therapeutical purposes has also been explored. A recent study showed that colicins can be used to disrupt biofilm integrity [223]. Moreover, when injected into the bloodstream of mice, pyocin S5 was observed to retain its functionality and to improve mouse survival to Pseudomonas infections [224].…”
Section: Discussionmentioning
confidence: 99%
“…Since colicin expression is tightly regulated by the SOS response system ( Gillor et al., 2008 ; Jin et al., 2021 ; Kamenšek et al., 2010 ), we focused on the expression of genes associated with DNA damage in E. coli biofilm compared to planktonic cultures. It has been shown in planktonic cultures that LexA protein binds to the promoter area of SOS-regulated genes and represses their expression ( Maslowska et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, further studies evaluating colicin production in biofilms revealed an increase of 7–9% in production rates, while in planktonic cultures the rates were 0.5–3% ( Majeed et al., 2015 ; Mulec et al., 2003 ; Riley and Wertz, 2002 ). In addition, although DNA-damaging agents are well known as key inducers to colicin production in planktonic environment, little is known about their impact in a biofilm ( Jin et al., 2021 ). For instance, colicin R was shown to be expressed mainly in biofilms but was undetected under planktonic conditions ( Rendueles et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DNase and RNase activities of colicins from E2 to E9 enable them to non-specifically degrade bacterial DNA and RNA 78 . Among these, colicin E2 exhibits potent and long-lasting bactericidal activity, and interestingly, it can specifically target bacteria in complex biological membranes 79 . Bacteriocins are capable of promoting the colonization of producer bacteria in specific niches over a decade, regulating the composition of the microbiota and affecting the host immune system 80 .…”
Section: Probioticsmentioning
confidence: 99%